FINANCIAL PERFORMANCE OF REGIONAL GOVERNMENTS IN INDONESIA'S SPECIAL AUTONOMOUS REGIONS: A COMPARATIVE ANALYSIS FOR ENHANCING ACCOUNTABILITY AND WELFARE - Mukhlis Suddin; Fitrian Rizky (SULTANIST: Jurnal Manajemen dan Keuangan, 2026)
The objective of this study is to examine disparities in local government financial performance across three Indonesian provinces with special autonomy status, namely Aceh, Papua, and West Papua and their implications for accountability and public welfare. Adopting a quantitative approach, the research employs census sampling across 65 regencies/cities over the 2019–2022 period, yielding 260 observations. Financial performance was evaluated using five key ratios: local revenue effectiveness, expenditure efficiency, regional financial independence, degree of decentralization, and regional financial dependence. Data were analyzed using independent-samples difference tests. Results indicate no significant differences in local revenue effectiveness ratios, but significant differences in expenditure efficiency, financial independence, degree of decentralization, and financial dependence ratios. These findings affirm Aceh's superior fiscal independence and decentralization relative to Papua and West Papua, which continue to depend heavily on central transfers, including special autonomy funds. The study contributes empirically by elucidating how variations in financial performance can serve as mechanisms to enhance local government accountability and public welfare in special autonomy regions.